AKUMULASI LIPID HATI DAN PROFIL LIPID DARAH TIKUS Sprague Dawley YANG DIINTERVENSI MINYAK SUPER OLEIN DAN OLEIN - Nurdin, Naufal Muharam; Rimbawan, Rimbawan; Marliyati, Sri Anna; Martianto, Drajat; Subangkit, Mawar (Jurnal Gizi dan Pangan, 2016)
The objective of this research was to analyze the effect of olein and super olein palm oil on blood lipid profile (total cholesterol, LDL cholesterol, HDL cholesterol, and triglyceride) and fatty liver condition of Sprague Dawley rats. The design used was pre and post test with control group design. The intervention run for 8 weeks using 20 rats which were divided into four treatments i.e: (1) standard-low fat feed and water (negative control/KN), (2) standard-low fat feed and dried egg yolk (positive control/KP), (3)standard-low fat feed and olein palm oil (B), and (4) standard-low fat feed and super olein palm oil (A). Results showed that blood lipid profile of rats at baseline were not different among treatment groups, while at midline super olein group has total cholesterol, triglyceride, and indirect LDL cholesterol lower than olein group. At endline, HDL and indirect LDL cholesterol of super olein group were different compared to olein group, while total cholesterol and triglyceride were not different between both groups. Super olein group had HDL cholesterol higher and indirect LDL cholesterol lower than olein group. Based on histopathology, lipid accumulation in the liver of Sprague Dawley rats in super olein group were lower than in olein group. The data showed that percentage of lipid droplet in super olein group (A) was 22.01%, while in olein group (B) was 40.43%.Keywords: blood lipid profile, fatty liver, palm oil, rats